HealthPathways: creating a pathway for health systems reform - Robinson, Suzanne; Varhol, Richard; Bell, C.; Quirk, F.; Durrington, L. (CSIRO Publishing, 2015)
Inefficiencies in the co-ordination and integration of primary and secondary care services in Australia, have led to increases in waiting times, unnecessary presentations to emergency departments and issues around poor discharge of patients. HealthPathways is a program developed in Canterbury, New Zealand, that builds relationships between General Practitioners and Specialists and uses information technology so that efficiency is maximised and the right patient is given the right care at the right time. Healthpathways is being implemented by a number of Medicare Locals across Australia however, little is known about the impact HealthPathways may have in Australia. This article provides a short description of HealthPathways and considers what it may offer in the Australian context and some of the barriers and facilitators to implementation.